Characterization of low calorie ready-to-serve peach beverage using natural sweetener, Stevia (Stevia rebaudiana Bertoni) - Ahmad, Uswa; Ahmad, Rabia Shabir; Mushtaq, Zarina; Hussian, Syed Makdoom (Progress in Nutrition, 2019)
Trend of fruits-based beverages has been increased due to their nutritional importance but sucrose used in them resulted in degenerative diseases. Stevia rebaudiana Bertoni natural, non-calorie sugar substitute can be used in the preparation of beverages for diabetes and weight maintaining approaches. The present study is focusing at preparation and characterization of peach ready-to-serve beverages with stevioside. Low calorie peach ready-to-serve beverages were prepared with stevioside from stevia aqueous extract at different levels (20, 25, 30 and 35 mg/100 mL) as sugar substitute. Antioxidant, physicochemical and organoleptic properties of functional beverages at 0 day to 60 days storage period were determined. The results depicted that stevioside improved the antioxidant profile of peach ready-to-serve beverages by significantly (P≤ 0.05) by increasing total phenolic, total flavonoid contents and DPPH activities from T0 to T4 (18.22±0.14-23.34±0.20 mg GAE/100g), (8.20±0.04-12.30±0.08 mg Catechin/100g) and (12.70±0.22-17.82±0.16 mg Trolox/100g) respectively. Regarding physicochemical characteristics, TSS (3.15±0.11-3.0±0.12 %), reducing (2.01±0.11-1.88±0.10 %), non-reducing (2.96±0.06-3.00±0.09 %) and total sugars (4.97±0.21-4.88±0.02 %) significantly affected among the treatments from T0 to T4. The results of organoleptical attributes significantly decreased with increasing the stevioside. During storage, antioxidant and organoleptic properties significantly decreased from T0 to T4. Physicochemical parameters including pH, non-reducing sugars and color significantly decreased while acidity, TSS, reducing and total sugars increased during storage but remained acceptable by sensory panelists. Conclusively, low calorie peach ready-to-serve beverages could be safe and promising nutracutical drink for the management of obesity, diabetes and its associated complications.